(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
The work represents the optimized solution for the selection of the reactive power compensation system for an on-grid photovoltaic plant with an installed power of 8 MW. The reactive power, of significant values, is mainly due to the length of the medium voltage cable that connects the photovoltaic plant to the connection station located at a distance of 10 km. Thus, a critical analysis is presented, with a technical-economic foundation of power factor correction solutions. The operation of the power plant’s correction system was monitored both during the day (while the panels were lit) and at night (without the panels lit). Special attention was paid to the influence of the energy quality parameters regarding the additional consumptions of the plant in the two situations. It was also considered to find an optimal solution for the maximum safety of the equipment in order to avoid reaching the critical operating temperature of the transformers in the plant. In addition, a detailed economic study was also carried out to justify the choice of the adopted solution (compensation with passive circuit elements - reactance coils) over the classic ones (adjusting the ignition angle of the inverters in the plant so that they work in inductive mode ).